Pengaruh Sistem Bagi Hasil Deposito Mudharabah Terhadap Minat Nasabah Berinvestasi Pada Bank Syariah - ., Rismawati; Rosita, Siti Ita (Institut Bisnis dan Informatika Kesatuan, 2014)
The Syariah Institution in Indonesia have a rapid growth from time to time, especially Syariah Bank. At this time, Indonesia is fourth country that have a great potential for development of syariah financial institute. The difference of principal and system is one of the reason that makes the public have an interest to invest in Syariah Institution, especially deposit investment that use mudharabah system for calculating profit. In 2009, after do spin off, PT Bank BNI Syariah successfully developed their business with adding more branch and increase the number of third party deposits. The objective of this research is to know Mudharabah deposit system, and how costumer’s interest to invest in Syariah Bank. And to know influence of the system that makes public interested in the deposit product. The location of this research is on PT Bank BNI Syariah Cabang Bogor as one of Syariah Bank that public has interest in it. This research uses descriptive method to know and show the relation between profit sharing system deposit system of mudharabah to the costumer’s interest to invest. The result of the research shows that the system to calculating profit that used by PT Bank BNI Syariah is revenue sharing, with deposit contract that they used is Mudharabah Mutlaqah. Based on examination to PT BNI Syariah’s annual report in 2010 – 2012, the number of deposits is increasing. It is because the product of PT Bank BNI Syariah is trusted by the customer. And beside that, the costumer knowing about Islamic Economic that uses profit sharing system is getting better. So, we can conclude that the profit sharing system of mudharabah deposits can affect the costumer’s interest to invest to deposit